PELATIHAN PEMBELAJARAN BERBASIS INTERNET BAGI GURU DI YAYASAN MUJAHIDIN KABUPATEN MALANG - Mohammad Maskan; Achmad Suyono; Bambang Soepeno; Asminah Rachmi (Publisher UPT P2M Politeknik Negeri Malang, 2019)
The purpose of this training is that the teachers at the Mujahidin Foundation can use the internet as a medium for learning. Community Service Activities were carried out on Sunday 3 November 2019 at the Mujahidin Foundation in Malang Regency. This activity is divided into several stages consisting of the preparation phase, the training phase and the preparation of activity reports. The material provided in this training covers the understanding of internet based learning, the scope, advantages and disadvantages of internet based learning as well as practicing the internet based learning process. During the training process the situation is educational, conducive and fun. This can be seen from the enthusiasm of the participants, the question and answer process and the complete participation of the participants from the beginning until the completion of the training event so that the material can be completed as a whole.